PENETAPAN KADAR KAFEIN PADA BUBUK TEH HITAM YANG BEREDAR DI PASAR DELI TUA MENGGUNAKAN SPEKTROFOTOMETRI UV - DIAN IKA PERBINA MELIALA (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
Tea is a drink that is very familiar in the world and is very common in everyday life. Tea is also the most consumed and favored beverage by the public after water. Besides being beneficial, tea also contains compounds that have a negative impact on the body, namely caffeine compounds. Caffeine is an alkaloid of the methylxanthine group which plays a role in increasing the work of psychomotor in the body, and side effects that can be caused are anxiety, irregular heartbeat, difficulty sleeping, tremors, diuresis and others. The purpose of this study was to determine the caffeine content in black tea powder circulating in the Old Deli market. This type of research is descriptive with a purposive sampling method. The analytical method used is qualitative with murexide and quantitative ultraviolet spectrophotometry with a wavelength of 267nm. The results of a qualitative analysis of all positive samples contained caffeine. The average quantitative yield of caffeine in brand A black tea powder was (4,82 ±0,0356)%, B brand black tea powder (4,89 ± 0,0173)% and C brand black tea powder (4,93 ± 0,0531)%. The validation test results obtained linearity r = 0,9984, LOD and LOQ is 0,8074 mcg/ml and 2,6914 mcg/ml ,% recovery = 100,07%, RSD = 0,33%. Based on the results of research conducted, it can be concluded that ultraviolet spectrophotometry can be used to determine caffeine levels in black tea powder.